The development of the student online learning patience scale (SOLPS) - Eryilmaz, Ali; Basal, Ahmet (SPRINGER, 2024)
Learning does not happen immediately; it takes time and effort. Thus, patience is a virtue required for any type of successful learning. Given the increasing prevalence of online learning, understanding students' patience is necessary to devise ways to sustain it. In this study, we define online learning patience as the ability to steadily continue studying or practicing in the online learning environments, even when it becomes difficult or takes a long time. The present study aimed to develop and validate a new instrument, the Student Online Learning Patience Scale (SOLPS), using a cross-sectional research design. The study participants, distributed across four distinct groups: Exploratory (n = 250 students), Confirmatory (n = 266 students), Validity for Impulsivity and Test-anxiety (n = 486 students), and Validity for Self-control (n = 232 students). The items in the scale were based on the literature and analysis of interviews with students. The scale structure was examined through Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA), and reliability and validity were tested. The final SOLPS consists of 10 items with one dimension and can be used to create teaching methods and strategies that increase students' online learning patience.
Keywords: Learning; Online learning; Online instructional environments; Patience; Scale development; SELF-CONTROL; SHORT-FORM; ACHIEVEMENT; IMPATIENCE; EVOLUTION; OUTCOMES; MODEL; SCMS; Education & Educational Research